Gait Imbalance Determination Using Foot Plantar Pressure Measurement - Jae Lim, Myung; Jin-Nam, Yun; Kun Chung, Dong; Man Kwon, Young (International Journal of Engineering and Technology, 2018)
The ability to walking is a basic component of human mobility, and gait, which is the pattern of walking, may help or harm human health depending on posture. Therefore, it is a part of smart health care to measure gait quality in real time and inform the user of the posture. This paper determines whether body balance is maintained during gait by using foot plantar pressure measurement among methods to determine the gait balance. Thus, it aims to investigate changes in body balance according to the weight of bags and the plantar pressure measurement system, and to implement a system that give a notice when an unbalanced gait occurs in the future study.Â